FEEDING PERFORMANCE OF BROILER CHICKEN FED DIETS WITH VARYING LEVELS OF PINTO PEANUT (ARACHIS PINTOI) LEAF MEAL - Marcos, Mark Joker L.; Gaffud, Oliva M; Mangoba, Alford Glenn C (Journal of Agriculture and Technology Management, 2020)
To evaluate the effect of pinto peanut leaf meal (PPLM) on the growth performance of broilers, 120-day old broiler Cobb 500 were divided to 4 groups and assigned to one of the 4 treatments with 0, 3, 6 and 9% PPLM following Completely Randomized Design. Significant ( P < 0.05) results were obtained in terms of broilers’ body weight on the 4 th up to 6 th weeks of the study, gain in weight, feed consumption, feed conversion ratio and efficiency (FCR and FCE). Treated birds with PPLM as fed diet were the most efficient feed converter and have the potential to increase rapid growth and improve vitality and livability of broiler chickens. Percentage rate of growth and dressing percentage with and without giblets were revealed to be insignificant. No statistical differences on the liver and pancreas weight were observed which indicates that there were no serious toxicity problems with the test diet. The Red Blood Cells (RBCs) analysis of the broiler chickens fed with PPLM was not significant across the treatments which fall within the normal range. In terms of the return over feed and chick cost, the broilers fed diet with 6% PPLM (T 3 ) produced the highest return amounting to PhP 79.17 per broiler, followed by the use of 9% PPLM (T 4 ), amounting to PhP 44.86 and followed by 3% PPLM (T 2 ) gaining PhP 39.50. The study suggested that PPLM at 6% inclusion can safely be used as feed ingredients to the broilers without any deleterious effect on the growth performance of broilers.